Effect of overall migration on tensile properties of biobased plastics containing polylactic acid, thermoplastic starch and zeolite - Busarin Chongcharoenyanon; Amporn Sane (Agriculture and Natural Resources, 2021)
Overall migration of biobased plastics were investigated. Different amounts of non-volatile substances that can migrate from food contact material or food packaging into the food were tested. Polylactic acid (PLA) and thermoplastic starch (TPS) were processed at different ratios of PLA-to-TPS of 60:40 and 80:20 with the addition of zeolite (Z5A) at 1% as a compatibilizer. Overall migration tests were conducted following The European Union Commission Regulation No. 10/2011. Migrants from the samples were extracted in food simulants using three standard testing conditions (OM1, OM2 and OM3). After extraction, the simulants were processed to determine the amounts of migrants and the samples were measured for tensile properties. Overall migration results were in the range 28.2–418.4 mg/dm2, indicating noncompliance with the overall migration Regulation limit of 10 mg/dm2. The testing condition at 70°C for 2 hr (OM3) showed the most promising application for food contact. Values for the tensile stress, tensile strain and Young’s modulus of samples with a PLA-to-TPS ratio of 80:20 were higher than for the samples using 60:40. The Young’s modulus of the sample composed of the PLA-to-TPS-to-Z5A ratio of 60:39:1 dropped to 475 MPa, while a significant reduction in tensile properties was recorded after contact with food simulants. Further investigations using lower temperatures and shorter extraction times are required to clarify the optimal conditions for commercial use.